2007
DOI: 10.1892/0891-6640(2007)21[308:dofdit]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fibrin Deposits in Tissues from Horses with Severe Gastrointestinal Disorders

Abstract: Background: In humans and experimental animals, disseminated intravascular coagulation (DIC) causes fibrin deposition in several organs, which eventually leads to ischemia and multiorgan failure.Hypothesis: Horses who died or were euthanized for severe gastrointestinal disorders could have fibrin deposits in different tissues.Animals: Tissue-organ samples collected during postmortem examinations on 66 colic horses with poor prognoses (eg, severe intestinal ischemia, enteritis, peritonitis), from 11 colic horse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 30 publications
4
28
1
1
Order By: Relevance
“…This finding is not surprising because the literature reports worse outcomes in horses with GI problems associated with a high number of coagulopathies and DIC 3,7,9,10 . Postmortem studies also found higher fibrin deposition scores in different organs of horses with colic diagnoses more commonly associated with DIC 8,38 . Nevertheless, previous results complementary with this study confirm that alterations of the coagulation profile in horses that survived tend to normalize during hospitalization regardless of the diagnosis a…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding is not surprising because the literature reports worse outcomes in horses with GI problems associated with a high number of coagulopathies and DIC 3,7,9,10 . Postmortem studies also found higher fibrin deposition scores in different organs of horses with colic diagnoses more commonly associated with DIC 8,38 . Nevertheless, previous results complementary with this study confirm that alterations of the coagulation profile in horses that survived tend to normalize during hospitalization regardless of the diagnosis a…”
Section: Discussionsupporting
confidence: 80%
“…A high percentage of horses with colitis (up to 36%) and ischemic lesions (up to 70%) have been reported to be in DIC, especially those disorders that have a poor prognosis, such as large colon volvulus 5–7 . Additionally, approximately 40% of horses with ischemic and inflammatory GI diseases of poor prognosis were found to have massive fibrin deposition in several organs at necropsy consistent with microthrombosis and DIC 8 . Thus, the severity of coagulopathies in horses with GI disorders appears to be related to the diagnosis.…”
mentioning
confidence: 99%
“…For each renal section, 10 fields were examined, and the average value from all of them was calculated. A 0 to 4 scoring system also was used for lung and liver sections, following previous descriptions . For lung and liver sections, 20 fields were examined, and the number of fields positive for the presence of intravascular fibrin in alveolar capillaries and hepatic sinusoids was counted, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In another study in mature horses, use of LMWH was linked by the authors with a better outcome (Cotovio et al . ). Heparin has not only antithrombotic but also anti‐inflammatory properties, which could be useful in the treatment of sepsis (de la Rebiere et al .…”
Section: Nutritional Supportmentioning
confidence: 97%